2019
DOI: 10.1371/journal.pone.0220137
|View full text |Cite
|
Sign up to set email alerts
|

Functional association of Loc1 and Puf6 with RNA helicase Dhh1 in translational regulation of Saccharomyces cerevisiae Ste12

Abstract: Loc1 and Puf6, which are localized predominantly to the nucleus, are required for the localization and translational repression of the ASH1 mRNA in the yeast, Saccharomyces cerevisiae . During its transport to the daughter cell, the ASH1 mRNA is translationally repressed via associations with She2, Loc1, and Puf6. Here, we investigated the roles of Loc1 and Puf6 in the translation of mRNAs other than that encoding ASH1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…Previous studies have suggested a role for Puf6 in the localization and translational repression of specific mRNAs 28 30 . However, in agreement with cell-biological studies 26 , 31 , we found that Puf6-GFP predominantly co-localizes with Gar1-mCherry, an established nucleolar marker (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have suggested a role for Puf6 in the localization and translational repression of specific mRNAs 28 30 . However, in agreement with cell-biological studies 26 , 31 , we found that Puf6-GFP predominantly co-localizes with Gar1-mCherry, an established nucleolar marker (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…6 g,h; Additional File 1 : Fig. S6h) motifs were associated with significantly enhanced protein expression, and the Puf6 site (UUGU [ 50 , 51 ]) was associated with a weak but statistically significant increase in expression (beyond the shuffled sequence control) (Fig. 6 i,j; Additional File 1 : Fig.…”
Section: Resultsmentioning
confidence: 99%
“…8 i, blue). These minimal effects may reflect the nature of Puf6 regulation, with known target genes displaying multiple Puf6 binding sites in their 3′ UTRs [ 50 , 51 ].…”
Section: Resultsmentioning
confidence: 99%
“…6e,f) and Puf5 (UGUANNNNUA [22,34]) (Fig. 6g,h) motifs were associated with significantly enhanced protein expression, and the Puf6 site (UUGU [36,37]) was associated with a weak increase in expression (beyond the shuffled sequence control) (Fig. 6i,j).…”
Section: Some Puf Protein Binding Sites Increase Protein Expression Imentioning
confidence: 97%
“…8i), and a weak increase in His3 protein expression. These minimal effects may reflect the nature of Puf6 regulation, with known target genes displaying multiple Puf6 binding sites in their 3′ UTRs [36,37].…”
Section: Comparison Of 3′ Utr Sequence Element Effects To Mrna Half-life Measurements Of Native Mrnasmentioning
confidence: 99%